2013
DOI: 10.1371/journal.pone.0080516
|View full text |Cite
|
Sign up to set email alerts
|

Computational Models Reveal a Passive Mechanism for Cell Migration in the Crypt

Abstract: Cell migration in the intestinal crypt is essential for the regular renewal of the epithelium, and the continued upward movement of cells is a key characteristic of healthy crypt dynamics. However, the driving force behind this migration is unknown. Possibilities include mitotic pressure, active movement driven by motility cues, or negative pressure arising from cell loss at the crypt collar. It is possible that a combination of factors together coordinate migration. Here, three different computational models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 50 publications
(86 reference statements)
0
49
0
Order By: Relevance
“…Passive mitotic pressure generated by cell division in the intestinal crypts, and subsequent gradual expansion in cell diameter along the crypt–villus axis, provides a plausible explanation for the steady continuous migration of epithelial cells (3, 4). Indeed, previous computational models suggest that these forces alone are sufficient to explain observed rates of cell migration, at least within the crypt (510). Conversely, other studies have reported continued epithelial cell migration or evidence for villus-to-crypt feedback in regulating proliferation rates when crypts were targeted with irradiation, ischemia, or cytotoxic agents (11–18).…”
mentioning
confidence: 98%
“…Passive mitotic pressure generated by cell division in the intestinal crypts, and subsequent gradual expansion in cell diameter along the crypt–villus axis, provides a plausible explanation for the steady continuous migration of epithelial cells (3, 4). Indeed, previous computational models suggest that these forces alone are sufficient to explain observed rates of cell migration, at least within the crypt (510). Conversely, other studies have reported continued epithelial cell migration or evidence for villus-to-crypt feedback in regulating proliferation rates when crypts were targeted with irradiation, ischemia, or cytotoxic agents (11–18).…”
mentioning
confidence: 98%
“…Macklin et al [155] have addressed ductile carcinoma's. A number of researcher has also been focused on intestinal crypts and epithelial tissues, studying e.g., cell organization and the role of basement membranes, and predicting the behavior of the tissue during steady state as well as after cell damage [35,37,52,[156][157][158][159][160][161][162][163].…”
Section: Achievements Limitations and Practical Usementioning
confidence: 99%
“…In the intestine, stochastic modelling of monoclonal expansion of stem cells, together with Cre/LoxP-based and other lineage tracing experimental strategies, have been instrumental in demonstrating that small intestinal epithelial stem cells are equipotent regarding their ability to occupy with their descendants the entire gland, divide symmetrically and be replaced at random according to a neutral drift pattern (Lopez-Garcia et al, 2010;Snippert et al, 2010;Leushacke et al, 2016). Among computational models, individual-based models have been widely used to describe the spatio-temporal dynamics of single cells, biomechanical properties, cell-cell and cell-matrix interactions, cell density effects and signalling pathways within the crypts (Pitt-Francis et al, 2009;Fletcher et al, 2012;Dunn et al, 2013;Pin et al, 2015). Both analytical and computational models of the epithelium are suitable for extensions, in alignment with data gathering, to account for interactions with the microbiome, immune system and enteric nervous system.…”
Section: Mathematical and Computational Modelling To Study Microbial-mentioning
confidence: 99%